2023
DOI: 10.3389/fcvm.2023.1199630
|View full text |Cite
|
Sign up to set email alerts
|

Photoplethysmography-documented atrial fibrillation in the first week after catheter ablation is associated with lower success rates

Martin Manninger,
Astrid N. L. Hermans,
Andrei-Antonio Caracioni
et al.

Abstract: AimsTo test the feasibility of postprocedural photoplethysmography (PPG) rhythm telemonitoring during the first week after atrial fibrillation (AF) ablation and its predictive value for later AF recurrence.MethodsPPG rhythm telemonitoring during the first week after the ablation procedure was offered to a total of 382 consecutive patients undergoing AF ablation. Patients were instructed to perform 1 min PPG recordings by a mobile health application 3 times per day and in case of symptoms. Clinicians assessed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 28 publications
0
3
0
1
Order By: Relevance
“… 23 This was first demonstrated by the TeleCheck-AF project during the COVID-19 pandemic, when patients were unable to visit a physician. 24 After the COVID-19 pandemic, PPG remained an attractive solution to monitor AF recurrence after ablation; 25 , 26 and to monitor AF burden with intermittent or continuous PPG. 27 …”
Section: Discussionmentioning
confidence: 99%
“… 23 This was first demonstrated by the TeleCheck-AF project during the COVID-19 pandemic, when patients were unable to visit a physician. 24 After the COVID-19 pandemic, PPG remained an attractive solution to monitor AF recurrence after ablation; 25 , 26 and to monitor AF burden with intermittent or continuous PPG. 27 …”
Section: Discussionmentioning
confidence: 99%
“…This could also be expanded to other settings, such as post-catheter ablation, where early recurrence may portend a greater risk of long-term recurrence. 14 …”
Section: Discussionmentioning
confidence: 99%
“… 47 In a pilot study from a single-center patients using digital devices 3 months after AF ablation had similar AF detection rates and a reduced need for additional ECG-monitoring compared to standard-of-care. 48 A caveat here is that validation of most devices has not been performed in the post-ablation population, which might be more prone to atrial tachycardias other than AF, which is notably more difficult to diagnose with digital devices using single-lead ECG or PPG. Prior studies have shown that 2 weeks of long-term intermittent monitoring by digital devices more effectively detected AF recurrences and had a higher patients’ usability than short continuous Holter monitoring.…”
Section: Atrial Fibrillation Management Supported By Digital Devicesmentioning
confidence: 99%